Estimated Land and Building Tax using Aerial Photography (Case Study: Tingkir District, Salatiga City) - Josef Allen; Frederik Samuel Papilaya (Politeknik Negeri Batam, 2020)
Salatiga, a city that borders directly and is surrounded by Semarang Regency. It has an area of ​​56.78 km2, with four sub-districts including, Sidorejo Regency, Argomulyo Regency, Tingkir Regency, and Sidomukti Regency, which covers 23 villages. The city of Salatiga has a fairly high population density with a proportion of more than 3300 inhabitants / km2. In this study took place in the Central Tingkir and Tingkir Lor areas by taking several points that are considered as housing as a case study. This study aims to estimate the price of land and building tax on an object of land and building tax. The process of this research uses aerial photo processing, where aerial photographs will be processed using professional software Agisoft photoscan to become an orthophoto, digital surface models and digital terrain models to obtain building area and land area data, then digital surface models and digital terrain models are processed . with ArcGIS 10.6 software using a raster calculator to get the height of the object to be used as the height of the building. The data obtained will be used to perform land and building tax calculations. The results of this study estimate the estimated land and building tax prices of at least IDR 37,313.00 and a maximum value of IDR 3,809,763.00.